TINJAUAN YURIDIS TERHADAP PENYELESAIAN SENGKETA DOMAIN NAME ANTARA PEMEGANG MEREK DENGAN PENDAFTAR DOMEIN NAME - budi kusuma (Journal of Law ( Jurnal Ilmu Hukum ), 2013)
abstractElectronic trading has spawned a new revolution, where there is a change in the way business is the sale and purchase of products and services. It is also concerned with the buying and selling of information, products and services through a network of computer telecommunications. Electronic trading helps traditional trade execution through a new way of transferring and processing information, because the information is at the heart of any trading activities. Information is electronically transferred from computer to computer, automatically.